Venetoclax – The Game-changer in Hematology (Indian Journal of Medical and Paediatric Oncology, 2020)
The introduction of small molecule inhibitors in many hematological malignancies made a landmark achievement in this field with a dramatic change in the survival outcome. Venetoclax is a B-cell lymphoma-2 inhibitor which has become the game-changer molecule in chronic lymphocytic leukemia and acute myeloid leukemia. This review is intended to summarize the mechanism of action, side effects, dosage, and different phases of clinical trials of this drug with review of literature.
Keywords: Acute myeloid leukemia; B-cell lymphoma-2 inhibitor; chronic lymphocytic leukemia; venetoclax